Progress on the Prevention of Esophageal Stricture after Endoscopic Submucosal Dissection - Peina Shi; Xiaoyun Ding (Gastroenterology Research and Practice)
Endoscopic submucosal dissection (ESD) has been widely accepted as an effective, minimally invasive treatment for superficial esophageal cancers. However, esophageal stricture often occurs in patients with large mucosal defects after ESD. In this review, we discuss various approaches recently researched to prevent esophageal strictures after ESD. These approaches can be classified as pharmacological treatments, esophageal stent treatments, and tissue engineering approaches. Most of the preventive approaches still have their limitations and require further research. With the improvement of current therapies, ESD can be more widely utilized as a minimally invasive treatment with minimal complications.